Implementasi Greenfoot 3.0.4 Untuk Membangun Aplikasi Pengucapan Bahasa Inggris Pada Arrobbany Course - Wire Bagye; Yuliana Yuliana (LPPM STMIK Lombok, 2018)
Arrobbany English Courses is an institutions which have only a single manager and tutor in guiding 67 students consisting of students from primary and secondary school level. In teaching and learning tutor often have difficulty in establishing a nice environment for some students would rather play than on learning. This causes the limited learning topic that can be delivered to students tutor each meeting. Therefore, it needs the right solution and does not incur costs to add a tutor or a native speaker, using a medium of learning. One of the media to learn the most widely used today is the computer as a proven way to speed up the delivery of learning topic and increase student interest. In this study Aplikasi Pembelajaran Bahasa Ingris is built to help tutor show the right pronoun to the students. Sound of pronoun will sounded when the picture clicked. There are seven learning menus in this application. Application development using Greenfoot with object-oriented programming concepts. Method development using SDLC, UML design and testing method using the Black-box testing. English Language Learning application is compiled into .jar extensions which can be run on the Windows operating system which have been installed JDK. Based on testing to 23 students indicates that the Aplikasi Pembelajaran Bahasa Ingris is exciting, produce the proper sound, and can replace the native speaker. The result of the assessment shows that average percentage are more than 82%.